Levodopa-induced motor complications associated with benserazide and carbidopa in Parkinson’s disease: a disproportionality analysis of the FAERS database - Qiu, Huaide; Liu, Cheng; Wang, Zhixiang (Frontiers in Pharmacology, 2025)
BackgroundLevodopa-induced motor complications are a significant concern in the treatment of Parkinson’s disease (PD). Dopamine decarboxylase inhibitors (DCIs) such as benserazide (BSZ) and carbidopa (CD) are commonly used in conjunction with levodopa to manage PD symptoms. However, their association with motor complications remains unclear.MethodsWe performed a retrospective pharmacovigilance analysis using the FDA Adverse Event Reporting System (FAERS) data from Q1 2004 to Q2 2024. The study included only adverse event reports (AERs) related to oral administration of drugs indicated for PD. We concentrated on motor complications, selecting two system organ classes (SOCs) associated with motor fluctuations and dyskinesia: nervous system disorders and general disorders/administration site conditions. Disproportionality analysis and Bayesian methods were utilized to identify and assess motor complication signals associated with BSZ and CD. A signal was deemed significant if it met the following criteria: reporting odds ratio (ROR) ≥ 3 with a 95% confidence interval (CI) lower bound >1, information component (IC) 95% CI lower bound >0, and empirical Bayes geometric mean (EBGM) 95% CI lower bound >2.ResultsThe analysis identified 8,744 AERs related to motor complications, recording 19,482 adverse events (AEs). The study highlighted motor complications such as dyskinesia, the on-off phenomenon, freezing episodes, and wearing-off, linked to the oral use of both BSZ and CD. Dyskinesia showed high RORs for both BSZ (16.5, 95% CI 14.76–18.45) and CD (13.81, 95% CI 13.02–14.65). The on-off phenomenon demonstrated a more pronounced ROR for BSZ at 170.74 (95% CI 145.03–201.01) compared to CD at 67.5 (95% CI 59.46–76.63). Wearing-off was notably higher for CD, with an ROR of 7.66 (95% CI 7.08–8.28), compared to BSZ’s ROR of 3.03 (95% CI 2.37–3.88).ConclusionThe findings indicate that the choice of DCI affects the risk profile of motor complications in PD. BSZ is associated with increased risks of dyskinesia and the on-off phenomenon, whereas CD is linked to a higher risk of wearing-off. Future research should explore the mechanisms underlying these differences to guide the selection of the most appropriate DCI for individual patients.